(untitled) (Teacher’s World: Journal of Education and Research, 2024)
This study is an attempt to understand the impact of politeness principles used by the teachers while exercising certain powers in their classes. In a language classroom, a teacher has to perform several roles, e.g. instructional, motivational, evaluative, and managerial. These roles associate a teacher in the milieu of exercising power (i.e. legitimate, referent, expert, reward, and coercive) in his/her classes. A teacher exercises powers through interactions. Effective interaction depends on appropriate use of politeness strategies. In this study, a mixed method approach has been used for collecting data. Four undergraduate level English classes of two teachers in two different universities within Dhaka city have been observed. The utterances of teachers have been scrutinized in order to identify teachers’ linguistic behaviour. The researcher recorded teachers’ utterances as qualitative data. Reduced data from classroom observations has been translated with a view to locating different types of powers exercised by the teachers. Questionnaire surveys have been used to collect quantitative data. This study has identified different types of power exercised by the teachers in their classes. Besides, it has provided a glimpse to what extent politeness strategies are being used by the teachers intentionally or unintentionally in order to save their students’ faces. Finally, the study has tried to show students’ perceptions towards teachers’ politeness and power exercise. Teacher’s World: Journal of Education and Res arch, 50(1): 79-94